Does Capital Structure Decisions Determine Dividend Payout Policy In Indian Iron And Steel Industry? An Empirical Study - Arindam Banerjee and Anupam De (Abhigyan, 2015)
This study is basically undertaken so as to investigate the independent variables on which the dependent variable i.e. the “Dividend Payout Ratio” depends upon for the firms belonging to the Indian Iron and Steel Industry. Multiple Regression Analysis has been carried out taking “Dividend Payout Ratio” as dependent variables and seven variables namely “Business Risk”, “Size of the Firm”, “Growth Rate”, “Earning Rate ”, “Financial Leverage”, “Debt Service Capacity” and “Degree of Operating Leverage”, as independent variables. The above independent variables influencing the Capital Structure Decisions of a firm has been taken into consideration after a thorough literature review. It is observed from the study that “Size of the Firm” and “Debt Service Capacity Ratio” are statistically significant to have an influence on Dividend Payout Ratio during the period under study. The result of the study has been validated by Factor Analysis approach